A new Pseudolepanthes (Pleurothallidinae: Orchidaceae) from Northwest Ecuador - Monteros, Marco F. (2021)
A new species of the genus Pseudolepanthes discovered in Carchi province, northwest Ecuador, is described here. The new species is compared with P. zunagensis from which it is distinguished by a longer inflorescence with successive vinaceous or pale-yellow flowers, an elongate arcuate column, and a lip with an erect, thick, widely rectangular central callus.